2017
DOI: 10.3389/fphys.2017.00716
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid-Regulated Antioxidant Mechanisms and Gene Expression Enhance Rosemary Performance under Saline Conditions

Abstract: Salinity stress as a major agricultural limiting factor may influence the chemical composition and bioactivity of Rosmarinus officinallis L. essential oils and leaf extracts. The application of salicylic acid (SA) hormone may alleviate salinity stress by modifying the chemical composition, gene expression and bioactivity of plant secondary metabolites. In this study, SA was applied to enhance salinity tolerance in R. officinallis. R. officinallis plants were subjected to saline water every 2 days (640, 2,000, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(95 citation statements)
references
References 71 publications
(83 reference statements)
12
71
0
3
Order By: Relevance
“…However, application of SA, GA and FU x1/10 significantly increased the CAT activity in roots compared to Fe deficient control. Similar results were reported in salt stressed rosemary plants where the application of SA (100-300 mg/L) increased CAT activity [50]. The CAT enzyme catalyze the decomposition of hydrogen peroxide (H 2 O 2 ) into oxygen and water [30].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, application of SA, GA and FU x1/10 significantly increased the CAT activity in roots compared to Fe deficient control. Similar results were reported in salt stressed rosemary plants where the application of SA (100-300 mg/L) increased CAT activity [50]. The CAT enzyme catalyze the decomposition of hydrogen peroxide (H 2 O 2 ) into oxygen and water [30].…”
Section: Discussionsupporting
confidence: 74%
“…Several studies reported positive effects on plant biomass under abiotic stress conditions after the application of SA, GA, SoA, MA, and LA, although none with respect to nutrient imbalance. Related to this, SA application at different concentrations, 0.5 mM (69 mg/L) in seeds of wheat [49], 100-300 mg/L sprayed in rosemary leaves [50] or 0.7-1.4 mM (96-193 mg/L) sprayed in sunflower [51] with high salinity showed a significant increase in FW. Applications in the nutrient solution of 1-2 mM (170-240 mg/L) GA in soybean under low temperatures [22] or applications of 0.75-1 mM (127-255 mg /L) GA in rice under salinity [20] increased the relative growth rate compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches had been adopted to control salinity adverse effects on plants and one of the more interesting is the use of salicylic acid. The effects of the use of salicylic acid on R. officinalis were studied by Elansary and collaborators . Salinity stress caused the reductions in α ‐pinene, β ‐pinene, and cineole along with increases in linalool, camphor, borneol and verbenone.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 93%
“…The effects of the use of salicylic acid on R. officinalis were studied by Elansary and collaborators. [174] Salinity stress caused the reductions in α-pinene, β-pinene, and cineole along with increases in linalool, camphor, borneol and verbenone. However, salicylic acid applications at 100-300 ppm largely reversed such effects of salinity.…”
Section: S Algeriensismentioning
confidence: 99%
“…It also influences fruit productivity, gas exchange, water composition and resistance development to plant diseases. However, the salicylic acid effect will depend on genetic and environmental factors, as well as the application method and dosage (El-Esawi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%